Human factors guide for the protection of onshore plants and offshore structures against fire and explosions - Terry, Ed (Steel Construction Institute, 2006)
This technical note is a "simple to use" guide to assist the awareness and implementation of the human factors in the design and operation of oil and gas facilities both onshore and offshore.
Keywords: Human engineering.; Petroleum refineries -- Fires and fire prevention.; Explosions -- Safety measures.; Structural analysis (Engineering); elektronické knihy; electronic books